AN OVERVIEW OF EDUCATION IN BRAZIL AND THE MAIN PUBLIC POLICIES THAT HAVE POSITIVELY IMPACT ON THE LIVES OF BRAZILIAN YOUTH - Vieira Bruce Ferreira, Débora (Revista Gênero e Interdisciplinaridade, 2023)
This work presents and analyzes the main public policies in the educational field implemented in Brazil, from 2003 to 2014, which had a positive impact on the democratization of youth access to higher education. The methodology used had as its starting point intuition in formulating hypotheses, enabling reflection to then obtain the time frame and target audience, obtaining the formulation of the problem. The next step consisted of organizing the information, transforming it into useful material for verification, and investigating primary sources, such as laws, decrees and bills; bibliographical research, in scientific articles, periodicals, master’s dissertations, and doctoral theses. At first, what we see is an approach to how higher education was structured in Brazil, from colonization to the new republic; then the discussion turns to the main public policies created or reformulated by the Federal Government, such as the University for All Program (PROUNI), the National Secondary Education Examination (ENEM) and the Unified Selection System (SISU), which contributed to expand youth access to higher education.